NUMERICAL ANALYSIS OF AN AUTOMOTIVE CAGE USED IN THE PERUVIAN MINING SECTOR - Angeles-Rocca, Junior V.; Alvarado-Silva, Carlos A.; de Oliveira, Geraldo César Rosário [UNESP]; De Souza, André Cristiano [UNESP]; de Azevedo Silva, Fernando [UNESP] (Centre for Evaluation in Education and Science (CEON/CEES), 2024)
A comparative analysis was conducted between the two structural formats employed in crafting internal roll cages in the Peruvian domestic market (Tubular and Laminar). The aim was to discern the protective effectiveness of each design. The examined cage design pertains to the most prevalent light utility vehicle used within the national mining sector. The computational analysis sought to derive Von Mises forces, resultant deformations, safety factors, and displacement along the applied force direction. This simulation was executed through finite element analysis, incorporating regulations sourced from the International Automobile Federation (FIA) and the Federal Motor Vehicle Safety Standards (FMVSS), which were adapted via analysis of Roll Over Protective Structures (ROPS). The results demonstrate a substantial safety factor in the laminar cage and a lesser concentration of Von Mises stresses in the tubular cage. Nonetheless, both structures experience significant deformations when subjected to lateral loads and at their respective joints. As a conclusion, it can be deduced that both structural configurations adopted in the crafting of interior roll cages adhere to specified standards. Notably, the laminar cage presents aesthetic and mechanical advantages. How-ever, the necessity for experimental testing to comprehend the structure's dynamic behaviour is underscored.
Keywords: automotive safety cages; finite elements; stress analysis; structural deformations